A purification treatment method of zinc-bromine flow battery electrolyte
Patent Information
- Application Number
- CN202611245088.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-17
- Publication Date
- 2026-10-30
AI Technical Summary
然而,该工艺在实际应用中除杂流程冗长、试剂消耗量大、固液分离困难且易产生二次污染,难以匹配大规模连续化生产需求;并且受限于反应热力学平衡与动力学条件,传统方法除杂后的电解液中仍含有一些微量的杂质离子无法脱除,影响电解液的品质,导致再生电解液的电化学性能无法完全恢复,严重制约了废电解液的高值化回收与规模化再利用
本发明通过采用化学氧化沉淀、电化学处理联合分步工艺,对锌溴液流电池电解液中的杂质离子进行了分离去除;两段工艺相互协同,化学氧化沉淀实现了大部分杂质的快速粗分离,电化学处理对残留杂质离子进行深度析出,实现了达到99%的杂质离子去除率。
Smart Images

Figure CN123018039A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of zinc-bromine flow batteries, and more particularly to a purification method for the electrolyte in zinc-bromine flow batteries. Background Technology
[0002] Zinc-bromine flow batteries, as one of the more commercially mature flow battery systems besides vanadium redox flow batteries, have initially been used in small-scale demonstrations and applications aimed at user-side arbitrage and improving power supply stability, thanks to their advantages such as modular design, low cost, and high safety. In recent years, with the large-scale grid connection of renewable energy sources such as wind and solar power and the advancement of new power system construction, zinc-bromine flow batteries, due to their long cycle life, easy scalability, and environmental friendliness, are gradually extending into the generation and grid-side sectors, with installed capacity and industrialization accelerating.
[0003] Electrolyte is the core working medium of a flow battery, and its preparation cost accounts for a significant portion of the total battery system cost. Furthermore, its concentration and volume directly determine the rated capacity and electrochemical performance of the flow battery. During long-term charge-discharge cycles, the effective concentration of zinc bromine in the electrolyte gradually decreases due to factors such as electrode side reactions, membrane ion cross-linking, water evaporation, pipeline corrosion, and external pollution. Simultaneously, impurity metal ions such as iron (Fe), copper (Cu), cadmium (Cd), and cobalt (Co) are inevitably introduced or enriched. These changes lead to battery capacity decay, decreased coulombic efficiency, increased polarization, and shortened cycle life. Recycling and purifying degraded or degraded electrolytes can effectively restore their electrochemical activity and capacity performance, enabling closed-loop utilization of key materials and significantly reducing the total life-cycle cost of flow batteries. It also avoids the ecological and environmental risks caused by the direct discharge of wastewater containing heavy metals and bromides, demonstrating significant economic and environmental benefits.
[0004] Currently, industrial purification of zinc-bromine flow battery electrolytes primarily employs a stepwise method, involving adjusting the pH and adding chemical precipitants or complexing agents to sequentially remove impurity metal ions such as Fe, Cu, Cd, and Co. However, this process is cumbersome in practical applications, consumes large amounts of reagents, is difficult to separate solids from liquids, and is prone to secondary pollution, making it unsuitable for large-scale continuous production. Furthermore, due to limitations in reaction thermodynamic equilibrium and kinetic conditions, trace amounts of impurity ions remain in the electrolyte after purification using traditional methods, affecting electrolyte quality and preventing the complete recovery of the electrochemical performance of the regenerated electrolyte. This severely restricts the high-value recycling and large-scale reuse of waste electrolytes. Therefore, there is an urgent need in this field to develop a highly efficient purification method for zinc-bromine flow battery electrolytes that does not introduce impurities and deeply removes trace impurities, thereby achieving stable recovery of electrolyte quality. Summary of the Invention
[0005] One of the objectives of this invention is to provide a purification method for zinc-bromine flow battery electrolyte, which can efficiently separate and remove impurity ions from the zinc-bromine flow battery electrolyte without introducing impurities.
[0006] The second objective of this invention is to provide an apparatus for purifying electrolyte in zinc-bromine flow batteries, which is simple in composition and easy to operate.
[0007] One of the solutions adopted to achieve the purpose of this invention is: a purification method for zinc-bromine flow battery electrolyte, comprising the following steps: (1) adding an oxidant to the zinc-bromine flow battery electrolyte and stirring until the reaction is complete; (2) adding a precipitant to the electrolyte obtained in step (1) and stirring until the reaction is complete; (3) filtering the electrolyte obtained in step (2) to remove the precipitate; and (4) electrolyzing the electrolyte obtained in step (3) to complete the purification.
[0008] Preferably, the impurities in the zinc-bromine flow battery electrolyte include at least one of chromium, manganese, iron, nickel, and copper.
[0009] Preferably, the oxidant in step (1) is hydrogen peroxide, the dosage is 1~5g / L, and the stirring reaction time is 0.5~1 hour.
[0010] Preferably, the use of hydrogen peroxide does not introduce other impurities into the zinc-bromine flow battery electrolyte system, thus improving the quality of the purified product.
[0011] Preferably, the precipitant in step (2) includes sodium N,N-dimethylthiocarbamate, with an addition amount of 30~300 mg / L, and the stirring reaction time is 0.5~1 hour.
[0012] Preferably, the filter membrane used for filtration in step (3) has a pore size ≤ 0.45 μm.
[0013] Preferably, the working unit used for electrolysis in step (4) includes at least an electrolytic cell, a positive electrode, a negative electrode, a power supply, and wires for connection.
[0014] Preferably, the positive electrode is a high-purity zinc sheet, and the negative electrode is a high-purity carbon sheet.
[0015] Preferably, the power supply is a constant voltage power supply with a voltage of 3-6V and a current density not exceeding 80 A / m. 2 .
[0016] Preferably, the electrolysis time in step (4) is 3 to 6 hours.
[0017] One of the solutions adopted to achieve the objective of this invention is: an apparatus for purifying electrolyte in zinc-bromine flow batteries, characterized in that it includes an oxidation tank, a precipitation tank, a filtration device, and an electrolysis device.
[0018] Compared with the prior art, the present invention has the following advantages: This invention employs a combined stepwise process of chemical oxidation precipitation and electrochemical treatment to separate and remove impurity ions from the electrolyte of a zinc-bromine flow battery. The two processes work synergistically: chemical oxidation precipitation achieves rapid coarse separation of most impurities, while electrochemical treatment deeply precipitates residual impurity ions, achieving an impurity ion removal rate of 99%.
[0019] This invention operates entirely at normal temperature and pressure, without the need for strong acids or alkalis, and is simple to operate, operates under mild conditions, and has strong equipment compatibility. Attached Figure Description
[0020] Figure 1 This is a comparison chart of battery energy efficiency before and after electrolyte purification treatment in Example 1. Detailed Implementation
[0021] To better understand the present invention, the following embodiments are further illustrations of the present invention, but the content of the present invention is not limited to the following embodiments.
[0022] The present invention adopts the following technical solution: S1 adds an oxidant to the electrolyte of a zinc-bromine flow battery. Some low-valence metal ions in the electrolyte, such as Fe... 2+ Co 2+ The oxidants oxidize Fe to higher valence metal ions, which can improve the efficiency of subsequent precipitation removal, and some Fe... 3+ During the stirring process, the electrolyte is separated and removed through hydrolysis and precipitation.
[0023] The oxidant is not limited, as long as it can oxidize impurity ions in the zinc-bromine flow battery electrolyte without introducing new impurity ions, including hydrogen peroxide and ozone. Considering the complexity of the equipment, ease of control, exhaust gas purification, dosage, and effect, hydrogen peroxide is preferred.
[0024] S2 adds a precipitant to the electrolyte. The precipitant is not limited, as long as it is a metal ion complexing agent that can separate and remove impurity ions in the electrolyte of zinc-bromine flow batteries, preferably sodium N,N-dimethylthiocarbamate.
[0025] Sodium N,N-dimethylthiocarbamate dissolves and dissociates to produce a dithiocarbamate anion (-S₂CN(CH₃)₂), which possesses bidentate chelating coordination properties. The two sulfur atoms in this anion structure have relatively large atomic radii, moderate electronegativity, and strong polarization and deformation capabilities, enabling it to act as a bidentate ligand for heavy metal cations (including Cu) in wastewater.2+ Pb 2+ Cd 2 + Hg 2+ Zn 2+ Ni 2+ (etc.) undergo coordination reactions to form thermodynamically stable five-membered ring chelates. The reaction process can be represented by the following general formula: M n+ + n NaS2CN(CH3)2→ M[S2CN(CH3)2] n ↓ + n Na + Where M n+ It is a heavy metal cation including Cu 2+ Pb 2+ Cd 2+ Hg 2+ Zn 2+ Ni 2+ wait.
[0026] In the aqueous phase reaction, sodium N,N-dimethylthiocarbamate forms strong interactions with metal ions, primarily through coordination bonds, via sulfur atoms. Its chelate products can further cross-link and polymerize into insoluble polymeric chelates with a highly cross-linked network structure by utilizing the multi-coordination properties of the metal ions. This highly cross-linked structure significantly increases the molecular weight and apparent density of the precipitate, causing it to rapidly aggregate into dense flocs in the liquid phase. This effectively overcomes the colloidal dispersion state easily formed by traditional hydroxide precipitation, greatly improving the sedimentation rate and subsequent solid-liquid separation efficiency.
[0027] S3 filtration removes sediment. S4 electrolysis completes purification. During electrolysis, a high-purity zinc anode is connected to the positive terminal of a DC power supply, and a high-purity carbon cathode is connected to the negative terminal of the DC power supply. After the current is applied, the metal cations in the electrolyte migrate directionally to the cathode surface under the influence of the electric field, gain electrons, and undergo a reduction reaction; while at the anode, an oxidation reaction occurs to maintain charge balance.
[0028] The anode reaction occurs during electrolysis, where the high-purity zinc sheet at the anode undergoes dissolution and oxidation, releasing electrons. Zn→Zn 2+ +2e
[0029] In the cathode reaction, heavy metal ions in the electrolyte gain electrons at the cathode surface, are reduced to elemental metals, and deposited. M n+ +ne →M↓ Where M n+ It is a heavy metal cation including Cu2+ Pb 2+ Cd 2+ Hg 2+ Zn 2+ Ni 2+ wait.
[0030] In addition, hydrogen evolution side reactions may occur at the cathode. By adjusting the electrolysis voltage and current density, the hydrogen evolution reaction can be suppressed and the current efficiency of heavy metal deposition can be improved.
[0031] The effects of the present invention will be described in detail below with reference to the embodiments.
[0032] Example 1 The zinc-bromine flow battery electrolyte in this embodiment was derived from a zinc-bromine flow battery that had been in actual operation for five years, with an operating energy efficiency of less than 70%. The mass concentrations of metal ions chromium, manganese, iron, nickel, and copper in the electrolyte were all greater than 5 mg / L, as shown in Table 1.
[0033] (1) Add hydrogen peroxide as an oxidant to the electrolyte of the zinc-bromine flow battery at a dosage of 1 mg / L and stir for 1 h.
[0034] (2) Add sodium N,N-dimethylthiocarbamate as a precipitant to the electrolyte obtained after oxidation in step (1) at a dosage of 30 mg / L and stir for 1 h.
[0035] (3) The mixed solution obtained in step (2) is filtered through a filter with a pore size of ≤0.45μm to obtain a preliminarily purified electrolyte.
[0036] (4) The electrolyte obtained in step (3) is placed in an electrolytic cell for electrolysis. The positive electrode of the electrolytic cell is a high-purity zinc sheet, the negative electrode is a high-purity carbon sheet, the reaction voltage is 3V, and the current density is 40A / m. 2 Electrolysis for 6 hours.
[0037] Example 2 The only difference between this embodiment and Embodiment 1 is that: In step (1), the amount of hydrogen peroxide added is 2 mg / L, and the reaction is stirred for 0.5 h; In step (2), the dosage of sodium N,N-dimethylthiocarbamate is 120 mg / L, and the reaction is stirred for 0.5 h. In step (3), the electrolysis voltage is 4V and the current density is 52A / m. 2 .
[0038] Example 3 The only difference between this embodiment and Embodiment 1 is that: In step (1), the amount of hydrogen peroxide added is 3 mg / L, and the reaction is stirred for 0.5 h; In step (2), the dosage of sodium N,N-dimethylthiocarbamate is 240 mg / L, and the reaction is stirred for 0.5 h. In step (3), the electrolysis voltage is 5V and the current density is 65A / m. 2 .
[0039] Example 4 The only difference between this embodiment and Embodiment 1 is that: In step (1), the amount of hydrogen peroxide added is 5 mg / L, and the reaction is stirred for 0.5 h; In step (2), the dosage of sodium N,N-dimethylthiocarbamate is 300 mg / L, and the reaction is stirred for 0.5 h. In step (3), the electrolysis voltage is 6V and the current density is 80A / m. 2 The reaction lasted for 3 hours.
[0040] The concentration of impurity metal ions in the zinc-bromine flow battery electrolytes obtained from the purification treatment in Examples 1 to 4 was tested, and the test results are shown in Table 1.
[0041] Table 1 Indicator Test Results
[0042] The zinc-bromine flow battery electrolytes obtained from the purification treatments of Examples 1-4 were injected into the same batch of batteries, and the battery performance was tested. The test results are shown in Table 2. The comparison of battery energy efficiency before and after electrolyte purification treatment in Example 1 is shown below. Figure 1 As shown.
[0043] Table 2 Performance test results.
[0044]
[0045] As can be seen from the data in Table 1, the impurity ion removal rates of the zinc-bromine flow battery electrolytes purified in Examples 1 to 4 all reached over 90%, with some reaching 97%. Specifically, the removal rate of chromium was highest in Example 4 (99.86%), similar to that of Example 2 (99.75%) and Example 3 (99.74%), and lowest in Example 1 (99.59%). The removal rate of manganese was higher in Example 1 (97.56%) and Example 2 (97.54%) than in Example 3 (97.37%) and Example 4 (97.38%). The removal rate of iron was highest in Example 2 (98.01%), followed by Example 1 (97.98%), and lower in Example 3 (97.07%) and Example 4 (97.02%). The removal rate of nickel was highest in Example 2 (92.31%), decreasing sequentially from Example 4 (91.95%), Example 3 (91.84%), to Example 1 (91.13%), but the differences between the examples were not significant (approximately 1 percentage point).
[0046] From the data in Table 2 and Figure 1 It can be seen that, during battery cycling, the zinc-bromine flow battery with purified electrolytes from Examples 1-4 showed significant improvements in charge-discharge efficiency, energy efficiency, and electrolyte performance compared to the original electrolyte. Specifically, regarding charge-discharge efficiency, the highest value in all 60 cycles was mostly attributed to Example 4 (only the 50th cycle showed a slightly higher value than Example 3), followed by Example 3. Example 1 was generally lower than Examples 3 and 4, but higher than or close to Example 2. Regarding energy efficiency, the highest value in all 60 cycles was attributed to Example 1, and its advantage remained stable (approximately 0.7-2.0 percentage points higher than other examples). The energy efficiencies of Examples 4, 2, and 3 varied but were all lower than Example 1.
[0047] Combining the data in Tables 1 and 2, we can see that: (1) The charge-discharge efficiency and the chromium removal rate show a certain positive correlation: Example 4, which has the highest chromium removal rate, has the best charge-discharge efficiency, while Example 1, which has the lowest chromium removal rate, has a relatively low charge-discharge efficiency. However, there is no obvious correlation between the charge-discharge efficiency and the removal rates of manganese, iron, and nickel.
[0048] (2) Although Example 1 had the lowest removal rate for chromium and a relatively low removal rate for nickel, its removal rates for manganese and iron were higher than those of Examples 3 and 4, and its energy efficiency was significantly better than other examples in all cycles. This indicates that moderate residual levels of manganese and iron (approximately 130~212 μg / L) may have a positive effect on energy efficiency, while excessive removal may lead to a decrease in energy efficiency; meanwhile, the level of nickel removal (within the range of 91%~92%) did not show a significant negative impact on energy efficiency.
[0049] (3) In summary, the optimal values for charge / discharge efficiency and energy efficiency do not belong to the same embodiment: when charge / discharge efficiency is the priority indicator, Embodiment 4 is optimal, while when energy efficiency is the priority indicator, Embodiment 1 is optimal. Therefore, in the zinc-bromine flow battery electrolyte purification process, the optimal residual range of impurity ions should be determined according to the target performance requirements, and it is not necessary to pursue the highest simultaneous removal rate of all ions. If both efficiencies need to be considered, the treatment conditions of Embodiment 1 can achieve the optimal energy efficiency while obtaining a high charge / discharge efficiency.
[0050] The above description is merely a preferred embodiment of the present invention, and should not be construed as limiting the scope of the invention. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of the present invention, and these improvements and modifications are also considered to be within the scope of protection of the present invention.
Claims
1. A method for purifying a zinc-bromine flow battery electrolyte, characterized in that, Includes the following steps: (1) Add an oxidant to the electrolyte of the zinc-bromine flow battery and stir until the reaction is complete; (2) Add a precipitant to the electrolyte obtained in step (1) and stir until the reaction is complete; (3) Filter the electrolyte obtained in step (2) to remove the precipitate; (4) The electrolyte obtained in step (3) is purified by electrolysis.
2. The purification method for the zinc-bromine flow battery electrolyte according to claim 1, characterized in that, The impurities in the electrolyte of the zinc-bromine flow battery include at least one of chromium, manganese, iron, nickel, and copper.
3. The purification method for the zinc-bromine flow battery electrolyte according to claim 1, characterized in that, The oxidant mentioned in step (1) is hydrogen peroxide, and the dosage is 1~5 mg / L. The stirring reaction time is 0.5~1 hour.
4. The purification method for the zinc-bromine flow battery electrolyte according to claim 1, characterized in that, The precipitant mentioned in step (2) includes sodium N,N-dimethylthiocarbamate, with an addition amount of 30~300 mg / L, and the stirring reaction time is 0.5~1 hour.
5. The purification method for the zinc-bromine flow battery electrolyte according to claim 1, characterized in that, The filter membrane used for filtration in step (3) has a pore size ≤ 0.45 μm.
6. The purification method for the zinc-bromine flow battery electrolyte according to claim 1, characterized in that, The working unit used for electrolysis in step (4) includes at least an electrolytic cell, a positive electrode, a negative electrode, a power supply, and wires for connection.
7. The purification method for the zinc-bromine flow battery electrolyte according to claim 6, characterized in that, The positive electrode is a high-purity zinc sheet, and the negative electrode is a high-purity carbon sheet.
8. The purification method for the zinc-bromine flow battery electrolyte according to claim 6, characterized in that, The power supply is a constant voltage power supply with a voltage of 3-6V and a current density not exceeding 80 A / m. 2 .
9. The purification method for the zinc-bromine flow battery electrolyte according to claim 1, characterized in that, The electrolysis time in step (4) is 3 to 6 hours.
10. An apparatus for purifying electrolyte in a zinc-bromine flow battery, characterized in that, It includes oxidation tanks, sedimentation tanks, filtration devices, and electrolysis devices.
